Gorlin syndrome: A case report - Abbas Darjani; Hojat Eftekhari; Nahid Nickhah (Our Dermatology Online, 2016)
Gorlin syndrome is a rare autosomal dominant disorder which characterize by multi-organ abnormities such as odontogenic keratocysts in the jaw, skeletal abnormities and multiple basal cell carcinoma etc. We report a case of this syndrome in a young man with palmar pits, multiple facial BCC, clacifications of the falx cerebri and bifid rib.